Differences Among States in Rural Veterans' Use of VHA and Non‐VHA Hospitals. Issue 1 (9th October 2015) - West, Alan N.; Weeks, William B.; Charlton, Mary E.
Abstract: Purpose: To understand how vouchers for non‐VHA care of VHA‐enrolled veterans might affect rural enrollees, we determined how much enrollees use VHA and non‐VHA inpatient care, and whether this use varies substantially between rural and urban residents depending on state of residence. Methods: For veterans listed in the 2007 VHA enrollment file as living in Arizona, Iowa, Louisiana, Tennessee, Florida, South Carolina, Pennsylvania, or New York, we merged 2004‐2007 administrative discharge data for all VHA hospitalizations with all non‐VHA hospitalizations listed in state health department or hospital association databases. Within states, rural and urban residents (RUCA‐defined) were compared on VHA and non‐VHA hospitalization rates, overall and for major diagnostic categories. Findings: Non‐VHA hospital use was much greater than VHA use, though it also was more variable across states. In states with higher proportions of urban enrollees, use of non‐VHA hospitals was lower for small or isolated rural town residents than urban residents; in the more rural states, it was greater. Rural enrollees also used VHA hospitals more than urban enrollees if they lived in the South, but they used VHA hospitals less in other states. Findings were consistent across principal diagnoses, except that in every state, rural veterans were hospitalized less often for mental disorders but more for respiratory diseases. Logistic regressions controlling several covariates consistently showed that very rural enrollees relied on VHA hospitals more than urban enrollees. Vouchers would likely increase non‐VHA use more in states with greater rural populations. Conclusions: Vouchers for non‐VHA inpatient care might have greater impact in rural states.